Chemical and mechanical properties of snake fangs. (14th March 2016) - Jansen van Vuuren, Ludwig; Kieser, Jules A.; Dickenson, Michelle; Gordon, Keith C.; Fraser‐Miller, Sara J.
Abstract : The composition of dental tissues and their interaction determines its mechanical properties. The mechanical properties and chemical composition of the teeth of extant reptiles are still poorly studied areas. As a preliminary study the fangs of four species of snakes and a human tooth were investigated through nanoindentation and Raman spectroscopy. The average elastic modulus values for the main body of the fangs ranged from 15.3 GPa to 24.6 GPa, and 19.1 GPa for the human dentine. Raman spectroscopy and principal component analysis (PCA) showed that snake fangs are similar in composition to human dentine, both of which comprised of hydroxyapatite and an organic matrix. The elastic modulus and hardness data were correlated to the Raman spectra using partial least squares regression (PLS). The spectral features which correlated with the elastic modulus would suggest that elastic modulus is dependent on the relative protein to mineral amounts in the tooth. The form of the phosphate and the relative levels of phosphate to organic components also appear to be governing factors for elastic modulus. The PLS of Raman spectra against the hardness gave very similar results. The small differences between snake fangs and human dentine appeared to be because of carbonate content, with higher levels of carbonate in the human tooth than the snake fangs. Snake fangs should be able to withstand large lateral forces. Human dentine aids in dissipating imposed loads. This similarity in the chemical composition of the snake fangs and human dentine supported the findings of the similarities in mechanical properties, which may be attributed to the similar functional demands of these biocomposites. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Four species of snake fangs and a human tooth were investigated through nanoindentation and Raman spectroscopy to relate the physical and chemical attributes of snake fangs. Snake fangs and human dentine were found to have similar mechanical properties and to be spectroscopically, hence chemically, similar. These similarities may be attributed to the similar functional demands of these biocomposites.